PERENCANAAN PROGRAM KEAGAMAAN DALAM MENINGKATKAN MUTU LULUSAN AGAMA - Aslikah Fardiana; Basuki (Pascasarjana IAIN Ponorogo, 2021)
SDN 1 Karanglo Lor strives to make a superior and quality institution among other educational institutions. This can be seen from the religious program in every class level. Intended so that students when graduating already have a strong religious knowledge that can help in the face of the rigors of life. Therefore, it is hoped that this state school will be able to excel in accordance with the expectations of the demands and needs of the times.So this research aims to describe the quality standards of graduates in the field of religion, the program, and planning at SDN 1 Karanglo Lor. The research method used is qualitative with the type of case studies and data collection methods using interviews, observation, and documentation. This research resulted in the quality standard of graduates in the religious fields at SDN 1 Karanglo Lor, that is able to read the Koran, understand recitation, memorize juz 30, be able to preach, be able to pray orderly, be fasting, can be recluse, can adhan, can pray, can memorize hadith, can write Arabic and can speak Arabic. The quality standard is an additional value of 8 National Education Standards. The religious program at SDN 1 Karanglo Lor is: a) Tahfidz based on quran, b) Hadrah and vocals based on social skills, and c) Madrasah diniyah based on pesantren. Planning religious programs using a comprehensive model. The plan is as a guide to outlining plans more specifically towards broad objectives.